Psychedelic replications in virtual reality and their potential as a therapeutic instrument: an open-label feasibility study - Kaup, Karl Kristjan; Vasser, Madis; Tulver, Kadi; Munk, Mari; Pikamäe, Juhan; Aru, Jaan (Frontiers in Psychiatry, 2023)
Background: Recent research has shown promising results for therapeutic benefits of psychedelics. One popular view claims that these benefits are mediated by the subjective experiences induced by these substances. Based on this, we designed a virtual reality experience, Psyrreal, that mimics the phenomenological components of psychedelic experiences. Aims: We aimed to investigate the therapeutic efficacy of Psyrreal and psychedelic VR experiences in treating depressive symptoms as well as investigate the effect of Psyrreal on subjective factors which have been suggested to mediate the therapeutic benefits of psychedelics. Methods: In this open-label feasibility study, thirteen participants with mild-to-moderate depression underwent a two-day therapeutic intervention implementing Psyrreal. Depressive symptoms were evaluated by the Emotional State Questionnaire (EST-Q2) at the start of the intervention and two weeks after. A thematic analysis of semi-structured interviews after Psyrreal was also conducted as an additional assessment of the method. Results: A two-day intervention implementing Psyrreal led to significant decreases in depressive symptoms at the two-week follow-up (n = 10, p = 0.007, Hedges’ g = 1.046) measured by the Emotional State Questionnaire (EST-Q2). The analysis of semi-structured interviews suggests that Psyrreal could lead to insight and alterations in the sense of self in some people. Conclusion: This work proposes a novel method using virtual reality to augment the treatment of psychological disorders as well as to precisely investigate the mediating subjective factors of the therapeutic effects of psychedelic substances. Our preliminary results suggest that VR experiences combined with psychological support show potential in treating depressive symptoms and further research into similar methods is warranted.